Another hidden cost of incentives: The detrimental effect on norm enforcement - Andreas Fuster; Stephan Meier (Federal Reserve Bank of Boston, 2009)
Monetary incentives are often considered as a way to foster contributions to public goods in society and firms. This paper investigates experimentally the effect of monetary incentives in the presence of a norm enforcement mechanism. Norm enforcement through peer punishment has been shown to be effective in raising contributions by itself. We test whether and how monetary incentives interact with punishment and how this in turn affects contributions. Our main findings are that free riders are punished less harshly in the treatment with incentives, and as a consequence, average contributions to the public good are no higher than without incentives. This finding ties to and extends previous research on settings in which monetary incentives may fail to have the desired effect.
Keywords: C72; C92; D23; H41; 330; public goods; experimental economics; norm enforcement; hidden costs of incentives; Normbefolgung; Öffentliches Gut; Trittbrettfahrerverhalten; Anreizregulierung; Soziales Verhalten; Soziale Gruppe